Keragaman Sifat Kualitatif pada Sapi Silangan PO dan Belgian Blue Menggunakan Analisis Komponen Utama - Jakaria Jakaria; Fuadi Zulkipli; Edwar Edwar; Mokhamad Fakhrul Ulum; Rudy Priyanto (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2020)
The purpose of this study was to determine the diversity of qualitative traits in PO, Belgian Blue and PO-Belgian Blue crosses using principal component analysis. The total samples of cattle used were 36 consisting of 8 heads Belgian Blue (4 males and 4 females), 17 heads Belgian PO-Belgian cross-breed (11 males and 6 females) and 11 PO heads (all females)). The diversity of qualitative traits observed were 17 characteristics namely plain body-color (WTP), combination body-color (WTK), horned (MT), humped (MP), sagging (MG), black tail tip color (WUEH), white tail tip color (WUEH), black eyelash color (WBMH), white eyelash color (WBMP), circle hair head (PRK), circle hair back (PRP), circle hair bracket (PRB), black nail color (WKH), nail color white (WKP), double muscle (PG), black muzzle (WMH) and white muzzle (WMP). Qualitative data were analyzed descriptively by calculating the proportion value, while the determinant variables of each breed were analyzed using the principal component analysis method (AKU) with the Minitab version 7 program. The results showed that the characteristics of qualitative traits in PO, Belgian Blue, and PO-Belgian Blue cross-breed cattle have a high diversity. PO and Belgian Blue cattle breeds can be clearly distinguished based on the characteristics of qualitative traits, whereas PO-Belgian Blue crossbred cattle have clusters that are close to PO cattle clusters. Found character traits for each cattle breed in both PO, Belgian Blue, and PO-Belgian Blue cross-breed. There are three characteristics of qualitative traits possessed in each cow nation, namely the variable circle hair head (PRK), circle hair back (PRP) and horned characters (MT). Based on the results obtained that the qualitative traits in cattle can be used as a distinguishing character between PO, Belgian Blue, and PO-Blue Belgian cross cattle breeds.